The term “God” between Al-Raghib Al-Isfahani (502 AH) and Al-Sabzwari (1414 AH) a semantic study in the Qur’anic vocabulary - ا.د اياد محمد علي; م.م طالب حمد جكي (مجلة اداب ذي قار, 2023)
The word “God” is one of the most common names among nations of different religions, beliefs, and times. Some researchers have wondered about the origin of this blessed name, is it Arabic or non-Arabic? It was said: It is not Arabic, and those who say so have their evidence, and it was said: It is Arabic due to the lack of evidence for what was mentioned of Arabization. The truth is that its meaning has been used in the past and in modern times with words that suit every language. The Canaanites used to call it (El), and from it say: Gabriel meaning angel of God, and Israel meaning servant of God. And the Persians: (God, Izd), the Jews: (Neil, the illusion, and the god), and the Buddhists call it: (Aum). The English: (Cod), the French: (Dieu), and the Germans: (Cott).